2022
DOI: 10.1021/acsmedchemlett.2c00161
|View full text |Cite
|
Sign up to set email alerts
|

S-Protected Cysteine Sulfoxide-Enabled Tryptophan-Selective Modification with Application to Peptide Lipidation

Abstract: Lipidation of peptides is a promising means of modification that can improve the therapeutic character of biologically active peptides. Here, a novel lipidation protocol for peptides is described. The C−H sulfenylation of indole in peptides using S-p-methoxybenzyl cysteine sulfoxide under acidic conditions in the presence of ammonium chloride, anisole, and triisopropylsilane enables late-stage tryptophan-selective peptide lipidation. This developed protocol has been used successfully for the lipidation of gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Then, the addition of the Cys(Acm)(O)‐decorated lipid 15 (1.2 equiv.) in HFIP containing 4 M diisopropylamine (DA) ⋅ HCl [30c] into the stapling reaction mixture with additional stirring at 15 °C for 1 h allowed the Trp‐selective C−H sulfenylation to proceed, generating the lipidated/stapled peptides ( 16 a and 16 b ) in 34 % and 28 % isolated yields, respectively (Figures 6b and S20). Peptide mapping of the obtained peptides using chymotrypsin indicated that the desired expected modifications occurred on the Tyr and Trp residues (Figure S21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the addition of the Cys(Acm)(O)‐decorated lipid 15 (1.2 equiv.) in HFIP containing 4 M diisopropylamine (DA) ⋅ HCl [30c] into the stapling reaction mixture with additional stirring at 15 °C for 1 h allowed the Trp‐selective C−H sulfenylation to proceed, generating the lipidated/stapled peptides ( 16 a and 16 b ) in 34 % and 28 % isolated yields, respectively (Figures 6b and S20). Peptide mapping of the obtained peptides using chymotrypsin indicated that the desired expected modifications occurred on the Tyr and Trp residues (Figure S21).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, in comparison with GLP‐1 (7–37) and non‐stapled lipidated GLP‐1 17 , [30c] the effect of the modifications in GLP‐1 peptides ( 16 a and 16 b ) was evaluated by an oral glucose tolerance test (OGTT) in wild‐type (WT) mice. After intraperitoneal administration of phosphate‐buffered saline (PBS) or the GLP‐1 peptides, insulin concentrations and blood glucose were measured during the OGTT (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…[107][108][109] We realized that S-protected Cys sulfoxides could be converted to the corresponding Cys(Cl) unit under acidic conditions in the presence of chloride anion in a redox-neutral manner. Under these conditions, S-p-methoxybenzyl Cys sulfoxide (Cys(MBzl) (O)) reacted efficiently with the Trp in peptide 121 to afford the tryptathionine-containing peptide 123 via an intermediate 122 110) (Fig. 30), and the success led to late-stage peptide lipidation.…”
Section: Rediscovery Of the Chemistry Of S-protected Cysteine Sulfoxi...mentioning
confidence: 99%
“…30), and the success led to late-stage peptide lipidation. 111) In addition, regioselective disulfide formation using S-protected Cys sulfoxides has become available. Further research efforts for applying the sulfoxide chemistry to peptide/ protein science, including late-stage peptide/protein modification and syntheses of peptides containing multiple disulfides and side chain-bridged peptides, have continued in our group.…”
Section: Rediscovery Of the Chemistry Of S-protected Cysteine Sulfoxi...mentioning
confidence: 99%
“…We report herein an advanced insulin synthesis that uses acidactivated S-protected cysteine sulfoxides for one-pot/stepwise disulfide bond formation as well as a subsequent lipidation sequence. [10]…”
Section: Introductionmentioning
confidence: 99%